2001
DOI: 10.1002/etc.5620200324
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons as inducers of cytochrome P4501A enzyme activity in the rainbow trout liver cell line, RTL‐W1, and in primary cultures of rainbow trout hepatocytes

Abstract: In order to investigate cell-specific differences in the response of in vitro models to environmental toxicants, we compared the capacity of nine polycyclic aromatic hydrocarbons (PAHs) to induce cytochrome P4501A (CYPIA) in primary rainbow trout (Oncorhynchus mykiss) hepatocytes and a rainbow trout liver cell line, RTL-W1. Induction of CYPIA was estimated from the catalytic activity of 7-ethoxyresorufin-O-deethylase (EROD) and compared by median effective concentration (EC50) values, induction spans, and benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 36 publications
5
33
0
2
Order By: Relevance
“…Hence these organic compounds are called as AhR agonists (Whyte et al 2000;Timme-Laragy et al 2007). In vitro studies with mammalian and piscine cell cultures and a few in vivo studies with some fish species have compared the EROD induction potency of different PAHs (Till et al 1999;Fent and Batscher 2000;Whyte et al 2000;Basu et al 2001;Behrens et al 2001;Willett et al 2001;Bosveld et al 2002;Billard et al 2004;Lu et al 2009). In general PAHs with five-or more rings are good CYP1A inducers but inconsistent information is available on EROD induction potential of PAHs containing two to four fused rings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence these organic compounds are called as AhR agonists (Whyte et al 2000;Timme-Laragy et al 2007). In vitro studies with mammalian and piscine cell cultures and a few in vivo studies with some fish species have compared the EROD induction potency of different PAHs (Till et al 1999;Fent and Batscher 2000;Whyte et al 2000;Basu et al 2001;Behrens et al 2001;Willett et al 2001;Bosveld et al 2002;Billard et al 2004;Lu et al 2009). In general PAHs with five-or more rings are good CYP1A inducers but inconsistent information is available on EROD induction potential of PAHs containing two to four fused rings.…”
Section: Discussionmentioning
confidence: 99%
“…Behrens et al (2001) compared the capacity of nine PAHs to induce CYP1A in primary rainbow trout hepatocytes and liver cell line RTLW1 and found anthracene, phenanthrene, fluoranthene and pyrene are non-inducing PAHs. However, a recent in vivo study demonstrated significant induction of EROD activity in golden grey mullet (Liza aurata) following phenanthrene exposure (Oliveira et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivariate correlations were tested by the non-parametric Spearman's correlation attending to the small number (6) Toxicity equivalents (TEQs) were calculated from the content of different samples in the parental PAHs (Querol et al, 2011;van Drooge et al, 2010), using previously reported toxicity equivalence factors for fish cells (Behrens et al, 2001;Fent and Batscher, 2000;Villeneuve et al, 2002) or YCM-RYA (Misaki et al, 2007). An additive action model was assumed, multiplying each PAH congener concentration by the respective TEQ factor and summing the resulting products.…”
Section: Statistical Analyses and Determination Of Teq And Bap Equivamentioning
confidence: 99%
“…[47,48,49]). For instance, to measure the dioxin-like activity, recombinant yeast cells, continuous teleostean and rodent cell lines and primary cell cultures from fish, birds and mammals have been used [50,51,52,53,54,55,56]. Differences of the gene induction response among cell systems derived from various species have been reported [53,54,57,58], which may relate to species-dependent ligandbinding affinity, in the expression level and structure of the receptors and their associated proteins, and in the ac-392 Fig.…”
Section: Gene Induction Assaysmentioning
confidence: 99%